2020
DOI: 10.1093/gerona/glaa246
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acids Whose Intracellular Levels Change Most During Aging Alter Chronological Life Span of Fission Yeast

Abstract: Amino acid deprivation or supplementation can affect cellular and organismal lifespan, but we know little about the role of concentration changes in free, intracellular amino acids during aging. Here, we determine free amino-acid levels during chronological aging of non-dividing fission yeast cells. We compare wild-type with long-lived mutant cells that lack the Pka1 protein of the protein kinase A signalling pathway. In wild-type cells, total amino-acid levels decrease during aging, but much less so in pka1 m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…The found alterations in metabolite levels as animals mature can indicate their possible link with the aging process. A review of the trajectories of the annotated metabolite levels changes showed that they resemble the age-related alterations in metabolites identified in the previously published studies [ 62 , 63 ]. Remarkably, at least some of the annotated metabolites (trehalose, BCAA) are involved in the earlier discovered metabolic signatures related to aging [ 62 ].…”
Section: Discussionmentioning
confidence: 61%
“…The found alterations in metabolite levels as animals mature can indicate their possible link with the aging process. A review of the trajectories of the annotated metabolite levels changes showed that they resemble the age-related alterations in metabolites identified in the previously published studies [ 62 , 63 ]. Remarkably, at least some of the annotated metabolites (trehalose, BCAA) are involved in the earlier discovered metabolic signatures related to aging [ 62 ].…”
Section: Discussionmentioning
confidence: 61%
“…Another study observed that protein-rich diets are associated with reduced availability of plasma NAD+ levels and inflammation in healthy middle-aged adults indicating that protein-deficient diets might promote longevity by improving cellular energy expenditure and expression of enzymes such as SIRTs (Seyedsadjadi et al, 2018 ). In terms of specific amino acids, it has been observed that amino acids can both promote and limit organismal lifespan and senescence, and thus amino acids can be used as markers of longevity (Rallis et al, 2020 ). In particular, the metabolism of branched-chain amino acids (BCAA) is associated with the regulation of human aging (Mansfeld et al, 2015 ).…”
Section: Primary Diet Constituents and Cellular Senescencementioning
confidence: 99%
“…Prostaglandin J₂ lifespan-extending effects depend on the mitochondrial fission protein Dnm1 and the G-protein-coupled glucose receptor Git3. The latter functions within the pka1 signalling pathway, known from separate studies to be largely implicated in lifespan regulation [ 10 , 11 , 45 ]. Additionally, mycophenolic acid (MPA) and acivicin, two chemicals that inhibit guanosine monophosphate (GMP) synthesis, extended chronological lifespan, indicating that an imbalance in guanine nucleotide levels impinges upon longevity.…”
Section: Non-competitive Screens For Factors Affecting Chronological ...mentioning
confidence: 99%
“…Ageing hallmarks and age-related diseases can be related to depletion or pathological physiology of either dividing adult stem cell pools or differentiated postmitotic cell populations [ 12 ]. In other words, organismal ageing has a cellular component that can be analysed in multiple levels (such as the levels of metabolome [ 11 ], transcription [ 13 , 14 ], protein translation and misfolding [ 15 ], cellular architecture and cytoskeleton [ 16 ]), with appropriate cellular models. Single-celled organisms such as the budding ( Saccharomyces cerevisiae ) and the fission ( Schizosaccharomyces pombe ) yeasts have been pivotal in this aspect providing molecular insights and having huge conceptual contributions in the field.…”
Section: Introductionmentioning
confidence: 99%